2021
DOI: 10.1016/j.jadohealth.2021.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Peer Norms are Unique Correlates of COVID-19 Vaccine Intentions in a Diverse Sample of U.S. Adolescents

Abstract: Purpose Recent studies have documented worrisome levels of hesitancy and resistance to the COVID-19 vaccine, including within the adolescent population. In this study, we examined attitudinal (perceived severity of COVID-19, vaccine-related concerns) and interpersonal (parent and peer norms) antecedents of adolescents’ intentions to receive the COVID-19 vaccine. Methods Participants were 916 adolescents (ages 12 – 17) from across the United States (47.3% male) represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
45
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 16 publications
9
45
0
2
Order By: Relevance
“…Although prior studies have considered the influence of social norms and the perceived vaccination status of peers, most have been focused on flu vaccination [ 28 , 29 ]. The only other study to our knowledge to assess the relationship with intentions to vaccinate children against COVID-19 was a direct survey of adolescents themselves, rather than parents/guardians [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although prior studies have considered the influence of social norms and the perceived vaccination status of peers, most have been focused on flu vaccination [ 28 , 29 ]. The only other study to our knowledge to assess the relationship with intentions to vaccinate children against COVID-19 was a direct survey of adolescents themselves, rather than parents/guardians [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This supports prior data that have identified factors such as parent and peer norms as particularly salient determinants of vaccine uptake. ( 17 ) It also highlights the important role pediatricians, and a pediatric offices, can play, in line with research that consistently identifies pediatricians as trusted sources for information on the COVID-19 vaccine. ( 16 ) Many indicated “other” as a reason for vaccine acceptance, suggesting more personal or nuanced factors influenced their decision to vaccinate.…”
Section: Discussionmentioning
confidence: 75%
“…Our survey also suggests that parents’, friends’, and schoolteachers’ attitudes toward COVID-19 vaccination may influence adolescents’ willingness to get vaccinated. Similarly, a diverse sample of adolescents in the United States showed that parent and peer norms were distinct predictors of adolescent willingness to receive vaccines [23]. Therefore, healthcare workers, parents, schoolteachers, and peers should be leveraged as advocates of COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%